2017
DOI: 10.1007/s12012-017-9404-4
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Activates Toll-Like Receptor 4 and Prevents Cardiac Fibroblast-to-Myofibroblast Differentiation

Abstract: Bacterial lipopolysaccharide (LPS) is a known ligand of Toll-like receptor 4 (TLR4) which is expressed in cardiac fibroblasts (CF). Differentiation of CF to cardiac myofibroblasts (CMF) is induced by transforming growth factor-β1 (TGF-β1), increasing alpha-smooth muscle actin (α-SMA) expression. In endothelial cells, an antagonist effect between LPS-induced signaling and canonical TGF-β1 signaling was described; however, it has not been studied whether in CF and CMF the expression of α-SMA induced by TGF-β1 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Moreover, they discuss many molecules, including microRNAs, cytokines and biochemical factors, membrane receptors, ion channels, cytoskeleton and extracellular matrix may become a promising target in VSMCs differentiation-related diseases [44]. Bolı´var et al recently reported that LPS induces TLR4 activation and prevents cardiac fibroblast-to-myofibroblast differentiation and that decreasedα-SMA expression played a role in this effect [45]. However, whether LPS-induced phenotypic modulation of VSMCs represents a new therapeutic target for proliferative vascular diseases warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they discuss many molecules, including microRNAs, cytokines and biochemical factors, membrane receptors, ion channels, cytoskeleton and extracellular matrix may become a promising target in VSMCs differentiation-related diseases [44]. Bolı´var et al recently reported that LPS induces TLR4 activation and prevents cardiac fibroblast-to-myofibroblast differentiation and that decreasedα-SMA expression played a role in this effect [45]. However, whether LPS-induced phenotypic modulation of VSMCs represents a new therapeutic target for proliferative vascular diseases warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This was accomplished by performing a parameter sweep of values for k dep while constraining k deg to satisfy the ratio determined previously and minimizing the sum of squared error (SSE) between the model fit and infarct experimental data. Wakefield et al, 1987;Campbell and Katwa, 1997;Campaner et al, 2006;Cartledge et al, 2015;Bolívar et al, 2017 k deg,latentTGFβ First-order degradation rate for latent TGFβ 5 0.0096 /hr Rollins et al, 1989 k act,latentTGFβ Activation rate of latent TGFβ to active TGFβ 5 & 6 0.045 Maeda et al, 2002;Hawinkels et al, 2007 Ancey et al, 2002;Fredj et al, 2005;Turner et al, 2007Turner et al, , 2009…”
Section: Network Model Inputsmentioning
confidence: 99%
“…In addition, inflammatory insults can also impair SMAD3 expression. For example, brains affected by Alzheimer disease are associated with decreased levels of SMAD3 [ 26 ], while SMAD3 phosphorylation (i.e., activity) is reduced in proximal tubular cells stimulated with IL-1 β [ 27 ] and in cardiac fibroblasts treated with LPS [ 28 ].…”
Section: Introductionmentioning
confidence: 99%